Comparison Of Microbial Humic Acid Produced By Aspergillus Niger X1 And Soil Humic Acid - N. GHOSH; S. GANGULY; A. K. BANIK (International Journal of Pharma and Bio Sciences, 2011)
A comparison is drawn between fungal humic acid produced by Aspergillus niger X1 and soil humic acid regarding elementary and functional groups analysis. Elementary and functional groups analysis show that unhydrolyzed fungal humic acid contained more H and N per unit weight, more alcoholic OH but lower CO2H and phenolic OH groups than unhydrolyzed soil humic acids. The C and N content of 6(N) HCl hydrolyzed humic acid are higher but the O content lower than the soil humic acids. Acid hydrolysis also increase the content of phenolic groups in fungal humic acid, this is accompanied by a decrease in alcoholic OH groups. There exist a number of similarities in analytical characteristics, especially surface functional groups.